PRINSIP STRICT LIABILITY TERHADAP KORPORASI DALAM PERKARA KEBAKARAN HUTAN AKIBAT PEMBUKAAN LAHAN: ANALISIS PUTUSAN 296/PDT/2020/PT.DKI): Strict Liability Principle Against Corporations in Forest Fire Cases Due to Land Clearing: Analysis Decision 296/Pdt/2020 DKI - Marshanda Cesilia Yaparto; Dhany Rahmawan (Faculty of Law, Universitas Trisakti, 2026)
This study examines the application of the strict liability principle to corporations in forest fire cases resulting from land-clearing by burning, as regulated under Indonesian environmental law and applied in the Jakarta High Court Decision No. 296/Pdt/2020/PT.DKI. Using a normative juridical method with statutory, conceptual, and case approaches, the research finds that Article 88 of Law No. 32 of 2009 obliges business operators to pay compensation and conduct environmental restoration without the need to prove fault. Forest and land fires (karhutla) are classified as unlawful acts under forestry and environmental legislation, providing a clear legal basis for imposing strict liability on corporations. In the cited decision, the court held PT Kaswari Unggul strictly liable for fires within its concession area and ordered compensation and environmental recovery. The study concludes that Indonesian law explicitly recognizes strict liability in forest fire cases and that the judiciary has effectively applied this principle to strengthen environmental law enforcement and protect the public’s right to a healthy environment.